Kajian Kualitas Perairan Laut Sekitar Muara Sungai Jelitik Kecamatan Sungailiat – Kabupaten Bangka - Wibowo, Mardi; Rachman, Reno Arief (Universitas Diponegoro, 2020)
Jelitik River is the main river and economic artery of Sungailiat District, Bangka Regency. Currently around the Jelitik River there is a Jelitik Fishing Port and is developed as an industrial area. In addition to the problems of sedimentation problems with the development of industrial estates and the presence of sand mining rich in tin ore on land and on the high seas it is feared that it will reduce the quality of the environment, especially the surrounding sea water. Therefore, this study is needed in order to find out the quality of waters in this estuary which can be used as a basis or baseline for the initial environment of this region if later this area will be developed as a port or industrial area. The method used in this study is field observation, water sampling, and laboratory analysis. Therefore, as an initial step, it is necessary to identify the quality of the waters in this estuary which can be used as the basis or initial environmental baseline of this area if later this area will be developed as a port or industrial area. Based on observations in the field of laboratory analysis of water samples, generally the quality of seawater around the estuary of Jelitik River still meets seawater quality standards both for port activities, marine tourism and for biota. Some parameters that exceed the quality standard include total suspended solid (TSS) which reaches 250 mg/l, total dissolved solids (TDS) which reaches 24,700 mg/l and nitrate content which reaches 0.38 mg/l. BOD value is 4.7 mg / l and COD is 46.4 mg / l, these parameters are still below the existing sea water quality standard.